2015
DOI: 10.1016/j.actamat.2015.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental sulfur on the structure of alumina scales formed on Ni-base alloys

Abstract: a b s t r a c tShort-term oxidation exposures of an alumina-scale forming c 0 -Ni 3 Al-based model alloy in air and O 2 + 0.1%SO 2 at 900°C revealed that the presence of sulfur can affect the kinetic competition between the h and a structural isomorphs of Al 2 O 3 . After 2 h exposure, metastable h-Al 2 O 3 growth predominated in air alone; whereas, a much larger percentage of stable a-Al 2 O 3 formed during oxidation in O 2 + 0.1%SO 2 . This promotion of a-Al 2 O 3 establishment was due to sulfur enrichment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…After 1 year of exposure at Randers, there was minimal attack of the nickel layer, and there was no clearly visible oxide [24], but after two years a distinct NiO layer could be observed. It would be expected that there was a NiO layer of a few microns after 7100 hours exposure based on measurements at 500 ºC, where a 1 µm layer was formed after 136 hours in O 2 [27] [32]. The stability of NiO, NiSO 4 , Ni and NiS in SO 2 gas has been investigated with respect to time at 540 o C, which showed that NiS was the stable compound while the other corrosion products decreased over time [33].…”
Section: Ni Coated Tubementioning
confidence: 99%
“…After 1 year of exposure at Randers, there was minimal attack of the nickel layer, and there was no clearly visible oxide [24], but after two years a distinct NiO layer could be observed. It would be expected that there was a NiO layer of a few microns after 7100 hours exposure based on measurements at 500 ºC, where a 1 µm layer was formed after 136 hours in O 2 [27] [32]. The stability of NiO, NiSO 4 , Ni and NiS in SO 2 gas has been investigated with respect to time at 540 o C, which showed that NiS was the stable compound while the other corrosion products decreased over time [33].…”
Section: Ni Coated Tubementioning
confidence: 99%